Edukasi Pemanfaatan Tanaman Asam Jawa dan Saffron sebagai Antidiabetes bagi Masyarakat Desa Tengah Pancur Batu, Deli Serdang - Pratiwi Rukmana Nasution; Masrah Masrah; Samihah Nasution (Jurnal Abdi Masyarakat Kita, 2023)
According to the International Diabetes Federation (2013), currently there are 382 million people living with diabetes. There are 316 million people with impaired glucose tolerance at high risk, an alarming number which is expected to reach 592 million people in 2035. Among the plants that have the potential as anti-diabetic agents are tamarind leaves and saffron plants. This community service activity uses the educational socialization method by conducting counseling and education on how to make tamarind and saffron drinks as anti-diabetic drugs. The purpose of this community service is to provide knowledge regarding education on the use of tamarind and saffron plants for the people of Tengah Pancur Batu Village. The results of Community Service obtained a good knowledge category with the achievement of the level of knowledge of participants before counseling and education in the less (60%) sufficient (27.5%) and good (12.5%) category, after counseling the results of the category increased significantly, namely less 0 ( 0%), enough (15%), and good (85%).